2015
DOI: 10.5306/wjco.v6.i4.64
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the effectiveness of abiraterone before and after docetaxel in patients with metastatic castration-resistant prostate cancer

Abstract: Prior chemotherapy may reduce the effectiveness of abiraterone in patients with metastatic CRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…A number of signaling pathways have been suggested to be involved in NSCLC progression, and have been targets of clinical and literature research. It was hypothesized that NSCLC may become resistant to therapies through feedback mechanisms that may compensate for targeted inhibition ( 55 ). Molecular targets of the VEGF and ERK/AKT pathways may simultaneously inhibit two important signaling pathways activated in NSCLC cells and may overcome one potential aspect of resistance to single-agent therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of signaling pathways have been suggested to be involved in NSCLC progression, and have been targets of clinical and literature research. It was hypothesized that NSCLC may become resistant to therapies through feedback mechanisms that may compensate for targeted inhibition ( 55 ). Molecular targets of the VEGF and ERK/AKT pathways may simultaneously inhibit two important signaling pathways activated in NSCLC cells and may overcome one potential aspect of resistance to single-agent therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rational use of multiple drugs is of vital importance. The optimal order of drugs has also been investigated [ 33 ]. Shameem and colleagues reported that postchemotherapy may lessen the efficacy of abiraterone in patients with mCRPC.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was conducted in strict accordance with the recommendations in the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health (13). Experimental protocols were approved by the Chinese Association for Laboratory Animal Sciences (Guangzhou, China) and Animal Health Products and the Committee on the Ethics of Animal Experiments Defense Research (Guangzhou, China).…”
Section: Methodsmentioning
confidence: 99%
“…Research suggests that tumors become resistant to therapy via feedback mechanisms that compensate for targeted inhibition (13). The upregulation of hypoxia-inducible factor 1 target genes, such as VEGF, has been implicated in RCC (12).…”
Section: Introductionmentioning
confidence: 99%